When Law Creates the Harm It Claims to Prevent: Prohibition, Corruption, Capture, and the Constitutional Review of Restrictive Law - Rubenstein, Elias (International Journal of Independent Research Studies, 2026)
This paper develops the concept of prohibition integrity as a legal-theoretical model for evaluating whether prohibitions, licensing regimes, and restrictive regulations reduce concrete harm or instead generate greater social and institutional harm. Building on prior work on conditionalized sovereignty and defensive sovereignty, the paper extends the analysis from permission-based autonomy and operational rights-disabling to the design of restrictive law. It argues that prohibitions should be assessed not only by their declared protective purpose, but by their operational consequences, including illegal market formation, corruption incentives, regulatory capture, criminalization of regulatory disagreement, democratic distortion, and operational rights-disabling. The paper identifies three core mechanisms of harm-producing prohibition: criminogenic prohibition, where bans suppress lawful supply without suppressing demand and thereby strengthen illegal markets; corruption-enabling prohibition, where vague or panic-driven legal categories may expand discretionary enforcement and valuable exceptions; and capture-based prohibition, where the public justification is harm prevention but the operational effect may be market protection, incumbent advantage, or cartel-like exclusion through law. It further argues that serious restrictive laws should be subject to civil-first analysis, democratic lawmaking review, constitutional friction, and periodic harm-reduction evaluation before becoming permanent. The paper introduces the Prohibition Integrity Test as a diagnostic screening tool rather than a mechanical formula. It identifies warning signs that require heightened justification, narrowing, conversion into regulation, independent review, or automatic expiry. The central claim is that no serious prohibition should be enacted or maintained unless the state can demonstrate net harm reduction.